When theater is an art (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This review examines the work The Art of Theatre, a text by Manuel de Macedo that details the practices and precepts governing theatrical activity in Portugal and Brazil during the second half of the 19th century. It was published as the 44th fascicle of the Biblioteca dos Povos e das Escolas (Library of Peoples and Schools) in 1884, a collection of booklets intended to introduce the reader to a certain universe of knowledge. The current edition, organized by Walter Lima Torres Neto, is complemented by a preface by Guilherme Felipe and an afterword by João Roberto Faria, scholars who situate and clarify the details of the original text for the contemporary reader.
Keywords: theatre; 19th century; theatrical life; brazilian theatre